Preventing relapse from wasting: the role of sociodemographic, child feeding, and health care determinants and of wasting prevention interventions in Burkina Faso and Mali - Brander, Rebecca L.; Toure, Mariama; Becquey, Elodie; Ruel, Marie T.; Leroy, Jef L.; Huybregts, Lieven (Elsevier, 2025)
Background Relapse among children treated for wasting is a major concern. We estimated the frequency and determinants of relapse to wasting in two populations exposed to PROMIS, an integrated wasting prevention and screening program. Methods Using longitudinal data from PROMIS trials in Burkina Faso and Mali, we calculated the incidence rate and period prevalence of relapse to wasting within 6 months in children who had ≥1 wasting episode ending when they were ≥6 months old for which they were treated and recovered (NBurkina Faso=247; NMali=220). We used backward elimination to select a multivariable model of sociodemographic, nutrition- and health-related determinants of relapse. We also evaluated if prevention interventions (behavior change communication (BCC) and/or small quantity lipid-based nutrient supplements (SQ-LNS) were associated with relapse, adjusting for confounders and trial arm. Results Relapse incidence was 2.6 per child-year in Burkina Faso (N=291 episodes) and 1.6 per child-year in Mali (N=300 episodes). In both countries, being fed the recommended food frequency or iron-rich foods after recovering from wasting was associated with lower risk of relapse. In Mali, longer wasting episodes, lack of minimally diverse diet consumption, and several caregiver/household characteristics were associated with lower risk of relapse. In both countries, receipt of BCC after recovery from wasting was associated with lower risk of relapse (Incidence rate ratio [IRR]Burkina Faso = 0.51 [95% confidence interval [CI] = 0.30, 0.86]; IRRMali = 0.26 [95% CI = 0.11, 0.65]), as was receipt of SQ-LNS (IRRBurkina Faso = 0.33 [95% CI = 0.16, 0.70]; (IRRMali = 0.43 [95% CI = 0.19, 0.94]), after adjustments. Conclusion Children being discharged from wasting treatment are a well-defined vulnerable population who stand to benefit from targeted post-discharge preventive interventions. BCC that includes advice on optimal infant and young child feeding practices and SQ-LNS may help prevent wasting relapse in at-risk children.